(untitled) (CIPEEX, 2025)
INTRODUCTION: The performance of cosmetic plastic surgeries has become increasingly common, raising questions about the impact of these interventions on patients’ mental health. The perception of improvements in appearance can influence psychological well-being, but there are also risks associated with unmet expectations and psychiatric disorders. OBJECTIVES: This article aims to examine the relationship between patients’ mental health and the performance of cosmetic plastic surgeries, exploring how these procedures affect psychological well-being and individuals’ quality of life. METHODOLOGY: A literature review was conducted based on articles and reviews published in specialized journals. The analysis included studies addressing the psychological impact of plastic surgeries, the role of body image, and the association with mental disorders. RESULTS: The reviewed studies show that undergoing cosmetic plastic surgeries can have varying effects on patients’ mental health. Some individuals report significant improvements in self-image and quality of life, while others face psychological challenges, including body dysmorphic disorders and unmet expectations. Preoperative psychological assessment can help identify risks and improve outcomes. CONCLUSION: The relationship between mental health and cosmetic plastic surgeries is complex and multifaceted. While some people may experience psychological benefits, others may face difficulties. Conducting an adequate psychological evaluation before the procedure is crucial to minimize risks and improve mental health outcomes for patients.